Difficulties in diagnosing Malassezia furfur bloodstream infection and possibility of spontaneous resolution in a patient undergoing chemotherapy for neuroblastoma: A case report. Issue 7 (July 2022) - Tetsuka, Nobuyuki; Muramatsu, Hideki; Iguchi, Mitsutaka; Oka, Keisuke; Morioka, Hiroshi; Takahashi, Yoshiyuki; Yagi, Tetsuya
Abstract: Malassezia furfur is a lipophilic, yeast-like fungus that forms part of the normal human skin microflora and is associated with a wide range of infections, such as pityriasis versicolor, folliculitis, and systemic infections in immunocompromised patients. Although matrix-assisted laser desorption/ionization time-of-flight mass spectrometry has enabled rapid identification of Malassezia species, it is still a challenge to diagnose systemic infections because Malassezia fungemia can often be missed by automated blood culture systems. We report a case in which M. furfur in blood was detected by the presence of yeast-like fungi in blood smears. Yeast-like organisms were observed in the blood smears of a 3-year-old boy, taken over 2 weeks without any symptoms. He had undergone several courses of chemotherapy for neuroblastoma via an indwelling central venous catheter (CVC) that was placed in his right anterior chest for 11 months. Although the blood cultures obtained from an automated blood culture system were negative, M. furfur growth was detected in the subcultured blood taken from the CVC. The CVC was removed, and the scheduled chemotherapy was postponed. No systemic M. furfur bloodstream infection occurred; the infection resolved spontaneously without any specific treatment; only prophylactic fluconazole was administered. M. furfur fungemia may not be diagnosable by an automated blood culture system. Further, M. furfur may not cause infections in humans even when administered intravenously. This report may lead to the discovery of factors related to human infectivity of this disease in the future.